Effects of Oxygen Transfer Limitation and Kinetic Control on Biomimetic Catalytic Oxidation of Toluene - 罗伟平 刘大为 孙俊 邓伟 盛文兵 刘强 郭灿城 (Chinese journal of chemical engineering, 2014)
Under oxygen transfer limitation and kinetic control, liquid-phase catalytic oxidation of toluene over metalloporphyrin was studied. An improved technique of measuring dissolved oxygen levels for gas-liquid reaction at the elevated temperature and pressure was used to take the sequential data in the oxidation of toluene catalyzed by metalloporphyrin. By this technique the corresponding control step of toluene oxidation could be obtained by varying reaction conditions. When the partial pressure of oxygen in the feed is lower than or equal to 0.070 MPa at 463 K, the oxidation of toluene would be controlled by oxygen transfer, otherwise the reaction would be controlled by kinetics. The effects of both oxygen transfer and kinetic control on the toluene conversion and the selectivity of benzaldehyde and benzyl alcohol in biomimetic catalytic oxidation of toluene were systematically investigated. Three conclusions have been made from the experimental results. Firstly, under the oxygen transfer limitation the toluene conversion is lower than that under kinetic control at the same oxidation conditions. Secondly, under the oxygen transfer limitation the total selectivity of benzaldehyde and benzyl alcohol is lower than that under kinetic control with the same conversion of toluene. Finally, under the kinetics control the oxidation rate of toluene is zero-order with respect to oxygen. The experimental results are identical with the biomimetic catalytic mechanism of toluene oxidation over metalloporphyrins.